The challenging child understanding, raising, and enjoying the five "difficult" types of children - Greenspan, Stanley I. 1941-2010; Salmon, Jacqueline 1943- (Addison-Wesley, 1995)
Identifying five "difficult" child personality types--sensitive, withdrawn, defiant, inattentive, and active/aggressive--a guide explains development from the child's perspective and offers strategies on how to make such differences positive.
Keywords: Parenting; Problem children; Erziehungsschwierigkeit; Eltern